Delayed hemoglobin switching and perinatal neocytolysis in mice with gain-of-function erythropoietin receptor - Divoky, Vladimir; Song, Jihyun; Horvathova, Monika; Kralova, Barbora; Votavova, Hana; Prchal, Josef T; Yoon, Donghoon (Journal of molecular medicine (Berlin, Germany), 2016)
UNLABELLED: Mutations of the truncated cytoplasmic domain of human erythropoietin receptor (EPOR) result in gain-of-function of erythropoietin (EPO) signaling and a dominantly inherited polycythemia, primary familial and congenital polycythemia (PFCP). We interrogated the unexplained transient absence of perinatal polycythemia observed in PFCP patients using an animal model of PFCP to examine its erythropoiesis during embryonic, perinatal, and early postnatal periods. In this model, we replaced the murine EpoR gene (mEpoR) with the wild-type human EPOR (wtHEPOR) or mutant human EPOR gene (mtHEPOR) and previously reported that the gain-of-function mtHEPOR mice become polycythemic at 3~6 weeks of age, but not at birth, similar to the phenotype of PFCP patients. In contrast, wtHEPOR mice had sustained anemia. We report that the mtHEPOR fetuses are polycythemic, but their polycythemia is abrogated in the perinatal period and reappears again at 3 weeks after birth. mtHEPOR fetuses have a delayed switch from primitive to definitive erythropoiesis, augmented erythropoietin signaling, and prolonged Stat5 phosphorylation while the wtHEPOR fetuses are anemic. Our study demonstrates the in vivo effect of excessive EPO/EPOR signaling on developmental erythropoiesis switch and describes that fetal polycythemia in this PFCP model is followed by transient correction of polycythemia in perinatal life associated with low Epo levels and increased exposure of erythrocytes' phosphatidylserine. We suggest that neocytolysis contributes to the observed perinatal correction of polycythemia in mtHEPOR newborns as embryos leaving the hypoxic uterus are exposed to normoxia at birth. KEY MESSAGE: Human gain-of-function EPOR (mtHEPOR) causes fetal polycythemia in knock-in mice. Wild-type human EPOR causes fetal anemia in knock-in mouse model. mtHEPOR mice have delayed switch from primitive to definitive erythropoiesis. Polycythemia of mtHEPOR mice is transiently corrected in perinatal life. mtHEPOR newborns have low Epo and increased exposure of erythrocytes' phosphatidylserine.
Keywords: Erythropoiesis; Animals; myši transgenní; Receptors, Erythropoietin; Genotype; Anemia; Polycythemia; polycytemie; Mice, Transgenic; erytrocyty; aktivační mutace; Neocytolysis; lidé; erytropoéza; Erythroid Precursor Cells; genotyp; Erythropoietin; Mice; STAT5 Transcription Factor; signální transdukce; Fetal polycythemia; myši; Signal Transduction; Humans; erythropoetin; regulace genové exprese; Hematocrit; transkripční faktor STAT5; fosforylace; Erythrocytes; Hemoglobins; receptory erythropoetinu; Human EPOR mutation; erytroidní prekurzorové buňky; Augmented Stat5 signaling; hemoglobiny; Prolonged primitive erythropoiesis; Gene Expression Regulation; zvířata; anemie; hematokrit; Phosphorylation; Gain of Function Mutation